Acetazolamide-Related Life-Threatening Hypophosphatemia in a Glaucoma Patient. Issue 4 (April 2015) - Hu, Ching-Yun; Lee, Bor-Jen; Cheng, Hsiang-Fan; Wang, Chen-Yu
<x xml:space="preserve">Abstract</x> Acetazolamide-related hypophosphatemia leading to cardiac arrest is extremely rare. Herein we report a 78-year-old female glaucoma patient who developed general weakness and acute respiratory failure, followed by cardiac arrest 1 day after taking acetazolamide. The patient was successfully weaned from the ventilator after correction of hypophosphatemia and fully recovered. As acetazolamide was shown to have the potential to cause a lethal side effect in stable glaucoma, the risk of hypophosphatemia should be kept in mind by ophthalmologists. An examination of serum metabolic panels may be indicated in patients at risk of hypophosphatemia.